Does High Unemployment Rate Cause High Suicide Rate? Evidence from Japan and South Korea - Huang, Chiung-Ju; Ho, Yuan-Hong (Journal of Reviews on Global Economics, 2016)
This study utilizes an asymmetric Granger causality test suggested by Hatemi-J (2012) to examine the causal relationship running from unemployment rate to suicide rate over the period of 1985 to 2012 in Japan and South Korea. Empirical results show that no Granger causality running from unemployment rate to suicide rate exists in Japan. However, results show that for South Korea, Granger causality exists running from a negative unemployment rate shock to a negative shock in suicide rate. More specifically, a decrease in unemployment rate leads to a decrease in suicide rate. Although the findings of this study do not support that an increase in unemployment rate has led to an increase in suicide rate for Japan and South Korea, a decrease in unemployment rate leads to a decrease in suicide rate in South Korea. Therefore, policy makers in South Korea could decrease unemployment rate to cause a decrease in suicide rate.